2020
DOI: 10.1111/cts.12891
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis Among the Level of IL‐35, Microvessel Density, Lymphatic Vessel Density, and Prognosis in Non‐Small Cell Lung Cancer

Abstract: The aim of this study was to determine the expression of IL-35 and the lymphatic vessel density (LVD) and microvessel density (MVD) in the pathological tissues from patients with non-small cell lung cancer (NSCLC) and to analyze their correlation with other common clinical prognostic factors, as well as patients' overall survival and progression-free survival. We analyzed the pathological characteristics of 130 patients with NSCLC and determined the IL-35 expression, MVD, and LVD changes in the pathological ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…STAT1 phosphorylation occurs upon IL-35 binding to gp130, whereas STAT4 phosphorylation occurs upon IL-35 binding to IL-12Rb2 (22). IL-35 exert immunosuppressive action through STAT1/STAT4 in T cells and STAT1 in B cells (23,24). IL-35 is a cytokine that is responsible for immune system maintenance and for this inhibition of immune responses, functioning by promoting the expansion of regulatory T cells (Tregs) and regulatory B cells (Bregs) while simultaneously suppressing effector T cells, Th1 cells, Th17 cells, and macrophages (25).…”
Section: Introductionmentioning
confidence: 99%
“…STAT1 phosphorylation occurs upon IL-35 binding to gp130, whereas STAT4 phosphorylation occurs upon IL-35 binding to IL-12Rb2 (22). IL-35 exert immunosuppressive action through STAT1/STAT4 in T cells and STAT1 in B cells (23,24). IL-35 is a cytokine that is responsible for immune system maintenance and for this inhibition of immune responses, functioning by promoting the expansion of regulatory T cells (Tregs) and regulatory B cells (Bregs) while simultaneously suppressing effector T cells, Th1 cells, Th17 cells, and macrophages (25).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Zhang et al showed that plasma IL-35 levels in NSCLC patients were significantly higher than those in healthy controls (55). Additionally, the overexpression of IL-35 was significantly correlated with prognostic factors such as T stage, lymph node metastasis, micro-vessel density, and tumor differentiation, and total survival time increased in patients with low expression of IL-35 (55). A recent study by Li et al showed that plasma IL-35 in the stage IV NSCLC patients was higher than that of the healthy group, and its expression levels were higher in the cachexia group than that of the non-cachexia group.…”
Section: Il-35 and Nsclcmentioning
confidence: 94%
“…IL-35 expression is increased in the serum and tumor tissue of NSCLC patients (17) and in bronchoalveolar lavage fluid (BALF) and serum of NSCLC patients undergoing immunotherapy (54), demonstrating that this cytokine can serve as a therapeutic target for NSCLC. The study by Zhang et al showed that plasma IL-35 levels in NSCLC patients were significantly higher than those in healthy controls (55). Additionally, the overexpression of IL-35 was significantly correlated with prognostic factors such as T stage, lymph node metastasis, micro-vessel density, and tumor differentiation, and total survival time increased in patients with low expression of IL-35 (55).…”
Section: Il-35 and Nsclcmentioning
confidence: 97%
“…These findings revealed that IL-35 secretion might be influenced by immune microenvironments and a variety of stimulants. In recent years, IL-35 was found to be involved in in multiple inflammatory diseases, autoimmune diseases and cancers, including type I diabetes, hepatitis, non-small cell lung cancer (14)(15)(16). Previous study also reported that IL-35 participated in bone metabolism (17,18).…”
Section: Introductionmentioning
confidence: 97%